Rearing Larvae of the Avian Nest Parasite, Philornis downsi (Diptera: Muscidae), on Chicken Blood-Based Diets. Issue 1 (4th August 2016) - Lahuatte, Paola F.; Lincango, M. P.; Heimpel, G. E.; Causton, C. E.
Abstract: Captive rearing of insect pests is necessary to understand their biology and to develop control methods. The avian nest fly, Philornis downsi Dodge and Aitken, is a blood-sucking parasite during its larval stage and a serious threat to endemic birds in the Galapagos Islands where it is considered invasive. In order to procure large numbers of flies for biological studies, rearing media and diets were trialed for rearing the larval stage of P. downsi under controlled conditions in the absence of its avian host. P. downsi eggs were obtained from field-caught female flies, and once eggs hatched they were reared on chicken blood for the first 3 d. Following this, three diets were tested on second- and third-instar larvae: 1) chicken blood only; 2) chicken blood, hydrolyzed protein and dried milk powder; and 3) chicken blood, hydrolyzed protein and brewer's yeast. Out of 385 P. downsi larvae tested, we were able to rear 50 larvae to the adult stage. The highest level of mortality was found in the first-instar larvae. Survivorship of second- and third-instar larvae was similar irrespective of diet and diet did not significantly influence larval or pupal development times; though larvae fed the diet with brewer's yeast developed marginally faster. Pupal weights were similar to those of larvae that had developed on bird hosts in the field. To our knowledge, this is the first effective protocol for rearing a hematophagous parasitic avian fly from egg to adult in the absence of a living host.